1997
DOI: 10.1007/s11745-997-0056-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary arachidonic acid on plasma lipoprotein distributions, apoproteins, blood lipid levels, and tissue fatty acid composition in humans

Abstract: Normal healthy male volunteers (n = 10) were fed diets (high-AA) containing 1.7 g/d of arachidonic acid (AA) for 50 d. The control (low-AA) diet contained 210 mg/d of AA. Dietary AA had no statistically significant effect on the blood cholesterol levels, lipoprotein distribution, or apoprotein levels. Adipose tissue fatty acid composition was not influenced by AA feeding. The plasma total fatty acid composition was markedly enriched in AA after 50 d (P < 0.005). The fatty acid composition of plasma lipid fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
58
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 35 publications
6
58
0
Order By: Relevance
“…18 When healthy volunteers were given Ϸ7 times the usual intake of AA (ie, 1.5 g/d) in a 7-week controlled feeding study, no effects on platelet aggregation, bleeding times, the balance of vasoactive metabolites, serum lipid levels, or immune response were observed. [5][6][7][8] Likewise, in a recent study from Japan, AA supplementation (840 mg/d for 4 weeks) had no effect on any metabolic parameter or platelet function. 19 Consistent with this, in observational studies, higher omega-6 PUFA consumption was associated with unaltered or lower levels of inflammatory markers.…”
Section: Omega-6 Pufas and Inflammationmentioning
confidence: 84%
See 1 more Smart Citation
“…18 When healthy volunteers were given Ϸ7 times the usual intake of AA (ie, 1.5 g/d) in a 7-week controlled feeding study, no effects on platelet aggregation, bleeding times, the balance of vasoactive metabolites, serum lipid levels, or immune response were observed. [5][6][7][8] Likewise, in a recent study from Japan, AA supplementation (840 mg/d for 4 weeks) had no effect on any metabolic parameter or platelet function. 19 Consistent with this, in observational studies, higher omega-6 PUFA consumption was associated with unaltered or lower levels of inflammatory markers.…”
Section: Omega-6 Pufas and Inflammationmentioning
confidence: 84%
“…The latter is converted to the metabolically important omega-6 PUFA arachidonic acid (AA; 20:4 omega-6), the substrate for a wide array of reactive oxygenated metabolites. Because LA accounts for 85% to 90% of the dietary omega-6 PUFA, this advisory focuses primarily on this fatty acid, recognizing that dietary AA, which can affect tissue AA levels, 5 may have physiological sequelae. 6 -8 LA comes primarily from vegetable oils (eg, corn, sunflower, safflower, soy).…”
Section: Omega-6 Pufasmentioning
confidence: 99%
“…In addition, it has recently been shown that a high intake of AA (1.7 g/d) by normal healthy subjects over a 50-day period does not modify lipoprotein distribution and apoprotein levels. 28 Finally, it is of interest to note that in the fish-diet population, but not in the vegetarians, a direct relationship exists between plasma Lp(a) and triglyceride levels, which is likely to be due to the lowering effect of n-3 PUFAs on both parameters. The mechanisms linking high fish intake and lower Lp(a) levels in plasma are unclear, because it is unknown at this time whether n-3 PUFAs affect apo(a) synthesis or metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Linoleic acid clearly has a hypocholesterolemic effect when substituted for dietary saturated fatty acids, reducing both LDL and HDL-C concentrations. However, arachidonic acid has little effect on plasma lipoprotein concentration (Nelson et al 1997). Numerous metabolic studies have shown strong cholesterol-lowering effects of vegetable oils rich in linoleic acid when substituted for dietary saturated fat (Grundy et al 1982).…”
Section: Omega-6 Polyunsaturated Fatty Acidsmentioning
confidence: 99%